2018
DOI: 10.1002/ejoc.201801140
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Oxidation of Benzylic and Aliphatic Alcohols Using a Bioinspired Cross‐Bridged Cyclam Manganese Complex with H2O2

Abstract: The cross‐bridged cyclam manganese complex Mn(Me2EBC)Cl2 efficiently catalyzes the oxidation of benzylic and aliphatic alcohols at pH 3 in a mixture of acetonitrile and water at room temperature. The environmentally benign and high oxygen content oxidant H2O2 was adopted. Conversions of the alcohols to the corresponding carbonyl compounds reached 98 % with good to excellent selectivity. In addition, several lignin model compounds were also catalytically oxidized under these conditions, with excellent conversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 47 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…benzaldehyde) were observed. While some reports exist with for example homogeneous Mn/H 2 O 2 systems [57,66], to the best of our knowledge this is the first example of the oxidation of this compound in the presence of a Pd/O 2 /water system [67][68][69]. This is encouraging for the transformation of more functionalized substrates.…”
Section: Application To the Oxidation Of Benzyl Alcoholsmentioning
confidence: 66%
See 1 more Smart Citation
“…benzaldehyde) were observed. While some reports exist with for example homogeneous Mn/H 2 O 2 systems [57,66], to the best of our knowledge this is the first example of the oxidation of this compound in the presence of a Pd/O 2 /water system [67][68][69]. This is encouraging for the transformation of more functionalized substrates.…”
Section: Application To the Oxidation Of Benzyl Alcoholsmentioning
confidence: 66%
“…Based on this, the potential of the NPs suspension was assessed for the oxidation of other substrates modelling the lignin structure under the same conditions [57] (Table 2). First we observed that the reaction was less efficient using 2-methoxybenzyl alcohol (entry 1) with a maximum yield of 21%.…”
Section: Application To the Oxidation Of Benzyl Alcoholsmentioning
confidence: 99%
“…The selective oxidation of alcohols to carbonyl compounds is one of the most important processes because the products are valuable in organic synthesis . Numerous methods for oxidation of alcohols have been developed involving the use of stochiometric oxidants such as chromium oxides, TBHP ( tert ‐butyl hydrogen peroxide), hydrogen peroxide, etc ., which cause environmental and high cost problems. From the viewpoints of enviroment and cost, selective oxidation of alcohols with molecular oxygen is extremely valuable and particularly attractive.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…This particular feature of these ligands led to the investigation of their utility in transition-metal-catalyzed processes. The Kochi and Burrows laboratories have separately evaluated these macrocyclic amines as ligands for nickel-mediated oxygen transfer processes. Additionally, these ligands have been applied to zirconium-catalyzed hydroamination, manganese- and iron-catalyzed oxidation, and electrochemical catalytic CO 2 reduction. Furthermore, the metal complexes of these polyamines have found applications as MRI contrast agents and radiopharmaceuticals …”
mentioning
confidence: 99%